Partilha de recursos e coexistência de populações sintópicas de Hyla nana e Hyla sanborni (Anura, Hylidae) - Menin, Marcelo (2002)
Ilyla nana and Hyla .sanborni are closed related species that occur in sympatry in several areas in South America. Here niche breadlh and overlap of both species were measured when in sympatry The measured niche dimensions were reproductive season, call site, diet, and multidimensional overlap. Males of Hyla nana are larger than those of II. sanborni. The reproductive season of II. sanborni was longer in permanent ponds, whereas II. nana presented larger reproductive season in the temporary pond. lhe call site was similar for both species, however II. sanborni called frorn higher perches than II. nana. Dipteious (Nematocera) was the most consumed item by both species in the tluee ponds, but in general, II. nana ingested larger prey than II. sanborni. The consumption of prey of both species was related to their availability in the environment. The multidimensional overlap between H. nana and II sanborni was higher in the permanent ponds than in lhe temporary pond, where II sanborni was rare. These species differed in abundance among ponds, consumed prey of different sizes, and probably fed in different periods. Moreovei, lhe data obtained suggest that the dynamic of resource partitioning change according to struclural differences of the ponds. Beside the great overlap found in the major niche dimensions analyzed the detected differences may be great etiough to allow their coexistence